Epidemiologic methods in physical activity studies - Lee, I-Min. (New York ; Oxford : Oxford University Press, 2009)
This text describes the associations between physical activity and major diseases. It emphasises the methods underpinning studies that can be conducted to elucidate these associations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Physical fitness -- Health aspects; Epidemiology